Framed. (San Francisco : Stephen Wirtz Gallery, 1991)
Messager, Annette ; Laub, Stephen ; Hellmuth / Reynolds ; Davis, Lynn ; Gerz, Jochen ; etc.
Framed, Stephen Wirtz Gallery, San Francisco, April 4 - May 4, 1991
boek